2013
DOI: 10.1103/physrevc.87.064313
|View full text |Cite
|
Sign up to set email alerts
|

Shape evolution and the role of intruder configurations in Hg isotopes within the interacting boson model based on a Gogny energy density functional

Abstract: The interacting boson model with configuration mixing, with parameters derived from the self-consistent mean-field calculation employing the microscopic Gogny energy density functional, is applied to the systematic analysis of the low-lying structure in Hg isotopes. Excitation energies, electromagnetic transition rates, deformation properties, and ground-state properties of the 172−204 Hg nuclei are obtained by mapping the microscopic deformation energy surface onto the equivalent interacting boson model Hamil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 80 publications
(193 reference statements)
15
83
0
Order By: Relevance
“…1) we observe in both isotopic chains the existence of rather sharp oblate and prolate energy minima, close in energy and separated by very high energy barriers, giving raise to shape coexistence. These findings are in qualitative agreement with recent calculations [19,23,25,26,30,31]. Looking in more detail the results from different calculations, one observes differences and similarities within the various approaches.…”
Section: A Equilibrium Deformationssupporting
confidence: 81%
See 2 more Smart Citations
“…1) we observe in both isotopic chains the existence of rather sharp oblate and prolate energy minima, close in energy and separated by very high energy barriers, giving raise to shape coexistence. These findings are in qualitative agreement with recent calculations [19,23,25,26,30,31]. Looking in more detail the results from different calculations, one observes differences and similarities within the various approaches.…”
Section: A Equilibrium Deformationssupporting
confidence: 81%
“…In particular, mean-field studies of structural changes with the Gogny interaction can be found in Ref. [25] for Hg isotopes and in Refs. [23,30,31] for Pt isotopes.…”
Section: Theoretical Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted, amongst other things, in the observation of strong staggering in the isotope shifts in the mercury isotopes [3], the discovery of triple shape coexistence in 186 Pb [4], and an early onset of deformation in the light polonium and platinum isotopes as evidenced through laser spectroscopy (see, e.g., [5]). The global trends of these experimental findings are reproduced by theoretical descriptions, such as phenomenological shape-mixing calculations and contemporary symmetry-guided models (e.g., [6,7]), and beyond mean-field approaches [5,8,9]. However, there is a lack of direct experimental information on the nature of the quadrupole deformation or on the mixing of the states belonging to the coexisting structures.…”
mentioning
confidence: 95%
“…Recently, the method of Ref. [31] was extended to handle shape coexistence [43] and applied to the neutron-deficient Pb [43] and Hg [44] nuclei and to some neutron-rich nuclei with mass A ≈ 100 [45,46].…”
Section: Introductionmentioning
confidence: 99%